The Fudge Family in Paris - Jaine, Tom (Petits Propos Culinaires, 2018)
The article consists of an short introduction to and a reprinting of a humorous poem containing many references to French food and culinary habits by the Irish lyricist, poet and writer, the biographer of Byron and Sheridan, Thomas Moore (1779–1852). It appeared in 1818 over the nom de plume ‘Thomas Brown the Younger, Editor of the Twopenny Post-bag’.